The effect of sports activities on the level of corona anxiety of the treatment staff of Ilam province with the mediator role of professional identity: With structural modeling approach - Shamseddin Rezaei; Ziba Gohari; Nooshafarin Farokhshahi (Shahrekord University of Medical Sciences, 2023)
Background and aims: Sports activities positively reduce mental disorders, especially in critical situations. Therefore, this research aimed to investigate the effect of sports activities on corona anxiety with the mediating role of professional identity in the treatment staff of Ilam province. Methods: This research was applied, and its method was descriptive-cross-sectional. The statistical population of the research was all the treatment staff of Ilam province, which was selected using Morgan's table and stratified sampling method, with 320 people for the sample. Four standard questionnaires on coronavirus anxiety of Alipour et al, the physical activity of Baecke et al, and the professional identity of Hao et al were used to collect data. The structural equation model (SEM) was used to analyze the data with the help of SPSS-22 and Amos-22 software. Results: The mean and standard deviation were obtained for the variables of sports activities ,(X̄=2.65, S=1.72) corona anxiety (X̄=3.23, S=2.25), and professional identity (X̄=3.30, S=3.77) The research showed that sports activities (β=-0.19, t=-2.808) and professional identity (β=-0.29, t=-2.624) have a negative and significant effect on corona anxiety, and the mediating role of professional identity in the relationship between sports activities and corona anxiety was also confirmed (β=0.55, t=-3.766). Conclusion: Based on the research results, the mediating role of professional identity was confirmed. Therefore, strengthening the professional identity through training causes the treatment staff to understand more about the need to participate in sports activities and, as a result, reduces their anxiety about the coronavirus.